Is glucose‐induced hypersecretion of glicentin after the revision surgery using Roux‐en‐Y gastric bypass related to improved glycemic control due to insulin hypersecretion in a type 2 diabetes patient without diabetes remission after laparoscopic sleeve gastrectomy? - Yukako Yamamoto; Osamu Sekine; Jun Ito‐Kobayashi; Ayane Nishida; Takeshi Togawa; Yuki Ozamoto; Yasumitsu Oe; Akeo Hagiwara; Masaki Kobayashi; Tadahiro Kitamura; Masanori Iwanishi; Akira Shimatsu; et al. (Journal of Diabetes Investigation)
ABSTRACT We report case details of a morbidly obese patient with type 2 diabetes mellitus (T2DM) who became a failure of diabetes remission after laparoscopic sleeve gastrectomy (LSG). He had a marked improvement of hyperglycemia after the revision surgery using Roux‐en‐Y gastric bypass (RYGB), where passage failure of a solid food intake at the gastric angle portion disappeared after the revision surgery. Interestingly, he showed improvements of insulin and a marked glicentin secretions with minor changes in glucagon related peptide 1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) secretions in the oral glucose tolerance test OGTT after the RYGB surgery compared with post‐LSG. Although a marked increase in glucose‐induced glicentin secretion after RYGB surgery with increased insulin secretion, further studies are needed to confirm if the increased glicentin secretion after RYGB surgery is linked to stimulation of insulin secretion.